Pengaruh Jenis Cangkang Telur Unggas terhadap Penurunan Kadar Fe Air Sumur - Galang Ciptaning Herjuno; Haryono Haryono; Tri Mulyaningsih; Bambang Suwerda (Buletin Keslingmas, 2026)
Well water often has problems such as a yellowish-brown color, a strong odor, and yellow deposits on the walls of the well. Based on preliminary studies in Morangan Village, Sindumartani, Ngemplak, Sleman, the iron content of well water was found to be 2.0 mg/L. This study aims to investigate the effect of different types of poultry eggshells as filtration media on reducing iron levels in well water in Morangan Village. The study design is a quasi-experimental study with a Pre-test-Post-test With Control Group Design. The study compares three types of poultry eggshells: chicken eggs, duck eggs, and quail eggs. The average reduction in iron content using chicken eggshells after filtration with a media thickness of 40 cm was 46.43%. The average reduction in iron content using duck eggshells with a thickness of 40 cm was 26.59%. The average reduction in iron content using quail eggshells as a filtration medium with a thickness of 40 cm was 77.10%. In conclusion, based on the results of the One-Way ANOVA test with a p-value of 0.000, it was found that the type of poultry eggshell used as a filtration medium significantly affects the reduction in Fe levels in well water. The quail eggshell filtration medium with a thickness of 40 cm is the most optimal filtration medium, with an average reduction in Fe levels in well water of 77.10%.